HUBUNGAN PENGETAHUAN ASUPAN GIZI DENGAN KEJADIAN KURANG ENERGI KRONIK PADA IBU HAMIL DI WILAYAH KERJA UPT. PUSKESMAS KALIJAGA KOTA CIREBON - Siti Elfiyah; Ani Nurhaeni; Lely Nurlaili (LPPM ITEKES Mahardika, 2021)
Knowledge of nutritional intake of pregnant women is the result of knowing about the amount of nutrition that enters through daily food consumption by pregnant women. Chronic lack of energy is an occurrence where pregnant women experience a shortage of nutrients that lasts for a long time or is caused by an imbalance in nutritional intake, so that the nutrients needed by the body are not fulfilled. This study aims to determine the relationship of nutritional intake knowledge with chronic energy deficiency events in pregnant women at Kalijaga Health Center. This research method uses analytical survey, with a cross-sectional research design. The population is children of pregnant women the total sample is 24 pregnant women. The sampling technique used total sampling. The instruments used were questionnaire sheets, Upper arm circumference and observation sheets. Data analysis used Spearman rank with significance value α = 0.05. The results of univariate analysis, knowledge of good nutritional intake (70.8%), those who have sufficient knowledge (12.5%), and those who have less knowledge (16.7%), while pregnant women who experience chronic energy deficiency amounted to (16.7%) and pregnant women who do not experience chronic energy deficiency (83.3%). Bivariate analysis with the Spearman rank test shows the p-value <ᾳ (p-value = 0,000: ᾳ = 0.05) r0.808, so that H0 is rejected, meaning that there is a very strong and positive relationship between knowledge of nutrient intake with less energy events chronic in pregnant women at UPT. Kalijaga Health Center, Cirebon City.